2006
DOI: 10.1097/01.sap.0000210180.72721.4a
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Complications in Free TRAM Flap Breast Reconstruction

Abstract: Awareness of risk factors and associated complications will lead to modification and individualization of surgical techniques in an attempt to limit these complications and continually improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
2
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(94 citation statements)
references
References 22 publications
3
85
2
4
Order By: Relevance
“…Several studies have examined the relationship between several patient characteristics (other than adjuvant therapy) and complications (2,6,(42)(43)(44)(45), but there was variation in the factors studied, and inconclusive results.…”
Section: The Effect Of Patient Characteristics On Breast Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have examined the relationship between several patient characteristics (other than adjuvant therapy) and complications (2,6,(42)(43)(44)(45), but there was variation in the factors studied, and inconclusive results.…”
Section: The Effect Of Patient Characteristics On Breast Reconstructionmentioning
confidence: 99%
“…Complications after breast reconstructive surgery are common (1)(2)(3)(4)(5)(6), and it has been shown that complications affect patient emotional well-Identifying independent risk factors for complications could have multiple advantages, such as making the treatment of patients with breast cancer requesting reconstruction more effective and aiding in selection of the best reconstruction method for each patient.…”
Section: Introductionmentioning
confidence: 99%
“…A purely technical reason for a failure may be too overly simplified. The evidence for this is provided by recent papers by Serletti [27][28]. A high-volume experienced surgeon with an enviably low 0.29% rate of failure in performing DIEP or free TRAM flaps has a 10x fold increase in failure to 2.9% when doing SIEA flaps [29].…”
Section: Discussionmentioning
confidence: 99%
“…A culture of success is reflected in their failure rates which are historically low [8][9][10][11][12]17,28,31]. It's important to mention that when a variety of flaps or new flaps are used the success rate goes down with a thrombotic rate of 17.4%, even at centers of excellence [28].…”
Section: Discussionmentioning
confidence: 99%
“…Continued tobacco use after a cancer diagnosis has been associated with various detrimental clinical outcomes such as shorter survival (Videtic et al, 2003;Fox et al, 2004;Sardari Nia et al, 2005;Zhou et al, 2006;Nguyenet al, 2010;Parsonset al, 2010;Kenfield, et al, 2011); increased risk of tumor recurrence or development of secondary malignancies (Do et al, 2003;Kawaguchi et al, 2006;Garces et al, 2007;Kaufman et al, 2008;Li et al, 2009;Joshu et al, 2011); poorer response to treatment and an increased risk of treatment toxicities (Monson et al, 1998;Dresler, 2003;O'Sullivan et al, 2003;van der Bol et al, 2007;de Jong et al, 2008;Waller et al, 2011;Petros et al, 2012); an increased risk of surgical complications (Moller et al, 2002;Barrera et al, 2005;Selber et al, 2006;Liu et al, 2011); and inferior bone marrow transplantation outcomes (Marks et al, 2009;Ehlers et al, 2011 ;Tran et al, 2011). Conversely, smoking cessation post-cancer diagnosis has been associated with better pain control and an improved quality of life (Garces et al, 2004;Baser et al, 2006;Daniel et al, 2009;Ditre et al, 2011).…”
Section: Introductionmentioning
confidence: 99%